2015
DOI: 10.1002/jbm.a.35583
|View full text |Cite
|
Sign up to set email alerts
|

Reducing bone cancer cell functions using selenium nanocomposites

Abstract: Cancer recurrence at the site of tumor resection remains a major threat to patient survival despite modern cancer therapeutic advances. Osteosarcoma, in particular, is a very aggressive primary bone cancer that commonly recurs after surgical resection, radiation, and chemotherapeutic treatment. The objective of the present in vitro study was to develop a material that could decrease bone cancer cell recurrence while promoting healthy bone cell functions. Selenium is a natural part of our diet which has shown p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 28 publications
(38 reference statements)
0
23
0
Order By: Relevance
“…One recent study indicated a significant decrease in long term proliferation of osteoblast-like sarcoma cells, while the proliferation of osteoblasts were two times higher, indicating the dual purpose of these nanoparticles. Additionally such superior performance was realized without the use of chemotherapeutics or any drugs [213]. These studies demonstrated not only their capability to induce osteogenesis via electrical, mechanical stimulation, but also simultaneously provide/stimulate anti-microbial/fungal functionalities to the scaffolds.…”
Section: Bone Regenerationmentioning
confidence: 99%
“…One recent study indicated a significant decrease in long term proliferation of osteoblast-like sarcoma cells, while the proliferation of osteoblasts were two times higher, indicating the dual purpose of these nanoparticles. Additionally such superior performance was realized without the use of chemotherapeutics or any drugs [213]. These studies demonstrated not only their capability to induce osteogenesis via electrical, mechanical stimulation, but also simultaneously provide/stimulate anti-microbial/fungal functionalities to the scaffolds.…”
Section: Bone Regenerationmentioning
confidence: 99%
“…Selenium (Se) is an essential trace element [ 1 , 2 ] that evinces antioxidant activity [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ], anti-inflammatory [ 2 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ], antimutagenic [ 26 , 27 ], anticarcinogenic [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] or chemopreventive [ 2 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], antiviral [ 2 ], antibacterial [ 45 , 46 , 47 , 48 ], antifungal [ 49 , 50 ] and antiparasitic effects [ 51 ,…”
Section: Biochemistry Of Seleniummentioning
confidence: 99%
“…The application of nanotechnology into biology has opened up immense opportunities in many areas, including tissue engineering3, drug delivery4, diagnostics5, imaging6, and fighting bacterial infections7. With the emerging need for novel antimicrobial agents, nanoparticles have been proposed to treat infections as they utilize different mechanisms for killing bacteria than conventional antibiotics, making them promising candidates to overcome current issues we are facing with antibiotic drug resistant bacteria8.…”
mentioning
confidence: 99%